Meningkatkan Kemampuan Berpikir Kreatif dan Pemecahan Masalah Matematis dengan Pembelajaran Metakognitif - Bayu Putra Irawan (Jurnal Pendidikan Matematika:Judika Education, 2020)
This research aims to find out the influence of mathematics learning with a metacognitive approach to creative thinking skills and mathematical problem solving students of Grade X TKR SMKS 6 Pertiwi Curup. This type of research is Class Action Research (PTK). The subject of this study was grade X students of SMKS 6 Pertiwi Curup which numbered 34 people. Data collection using observation sheets and test sheets. The results showed that the implementation of class actions with metacognitive learning performed well. Students' mathematical creative thinking skills improved, if in the pretest results only 5 students achieved the good category, then in the posttest results as many as 24 students have reached the good category. Indicators solve problems in less categories in pretes and in posttest test results mathematical troubleshooting capabilities show an improvement. The pretest results did not reach either category, so in the posttest results for cycle I as many as 11 students reached the good category and in the posttest result cycle II as many as 28 students were able to achieve the good category. In conclusion, learning mathematics with an effective metacognitive approach improves the creative thinking and mathematical problem solving skills of students in Grade X of SMKS 6 Pertiwi Curup. Keywords: Creative Thinking Ability, Students' Mathematical Problem Solving, Metacognitive Learning